1979
DOI: 10.1071/pp9790595
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Characteristics of Aminoacyl β-Naphthylamidase Activities in Wheat Seedlings

Abstract: Gel electrophoretic studies have revealed that crude extracts from various tissues of wheat seedlings contain two major enzymes capable of hydrolysing aminoacyl �-naphthylamides. A third enzyme which exclusively hydrolyses the �-naphthylamides of the imino acids proline and hydroxyproline has also been demonstrated in wheat leaves. The pH optimum for �-naphthylamidase activity against phenylalanine �-naphthylamide in crude extracts was 7.4. The two major enzymes differ with respect to their substrate specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
20
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…This same trend was reported by Waters and Dalling (29), showing an increased ,3-naphthylamidase activity in wheat seedling leaves to day 7 followed by a continuous decrease. In oat leaves placed in the dark, AP activity against three substrates declined steadily (12).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…This same trend was reported by Waters and Dalling (29), showing an increased ,3-naphthylamidase activity in wheat seedling leaves to day 7 followed by a continuous decrease. In oat leaves placed in the dark, AP activity against three substrates declined steadily (12).…”
supporting
confidence: 75%
“…Significant inhibition occurred in the presence ofboth strong chelating (1,10-phenanthroline and Bath) and sulfhydryl (pCMB) type inhibitors. Other investigators have reported similar results; three maize APs (27) and other APs in pea (4,9), wheat (29), and Euonymus (24) also showed significant inhibition by both sulflhydryl inhibitors and chelating agents.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Although considerable quantities of mitochondria and peroxisomes were occluded within the intact chloroplast band, chloroplast-free zones of peroxisomes (fractions 5-8) and mitochondria (fractions 13-16) were also located in the gradient. The cytoplasm, identified by glucose-6-P dehydrogenase (fractions [26][27][28][29], was contained in the supernatant on top of the sucrose gradient. The supernatant also contains the contents of broken organelles, including the vacuoles, which are too large to pass intact through the 20-,um mesh used to break the protoplasts.…”
Section: Resultsmentioning
confidence: 99%
“…Protein degradation has been envisaged as a process initiated by endopeptidase action and continued through the action of exopeptidases, including aminopeptidases, carboxypeptidase, and di-and tri-peptidases to eventually release amino acids for storage and/or transport (24). Characterization of these enzymes (5,15,22,29) has shown that, despite their common role in protein breakdown, they have few similarities with respect to the conditions required for optimal in vitro activity. These differences, particularly differences in optimum assay pH, have led to suggestions of enzyme compartmentalization as a means of regulating protein degradation, since the plant cell contains a number of localized pH zones by virtue of its various organelles.…”
mentioning
confidence: 99%